Evaluation of Chemical, Phyto Chemical and Methane Mitigation Potential of Turmeric (Curcuma longa) by In-vitro Study - Balamurugan, R.; Radhakrishnan, L.; Karunakaran, R.; Gnanaraj, P. Tensingh; Vijayarani, K. (International Journal of Livestock Research, 2020)
The nutritional composition, phytochemical and methane mitigation potential of turmeric (Curcuma longa) was evaluated. Turmeric contained 14.34, 14.73, 5.42, 2.34, 9.52 and 53.65 per cent moisture, crude protein, crude fibre, ether extract, total ash and nitrogen free extract, respectively. Qualitative assessment of Phytochemical screening of alkaloids, flavonoids, tannins, phenol, saponins, carbohydrates, proteins, amino acids, phytosterols and terpenoids in water and methanol extract revealed presence of all these compounds except proteins and amino acids. The turmeric was also evaluated in 20mg, 40mg, 60mg, 80 mg, and 100mg dose level in in vitro rumen fermentation studies for its methane mitigation potential. The highest methane mitigation potential (4.34±1.14) i.e. methane production per 100 mg truly digested substrate was observed in 80 mg turmeric dose level which was significant (P<0.05). It could be concluded that turmeric is a good protein source and its supplementation at 80 mg dose level in vitro reduced methane production.